A walk in the woods [videorecording (DVD)] - Redford, Robert; Thompson, Emma; Nolte, Nick; Steenburgen, Mary; Bryson, Bill (Broad Green Pictures, 2015)
Bill Bryson, instead of retiring to enjoy his loving and beautiful wife and large and happy family, challenges himself to hike the Appalachian Trail: 2,200 miles of America's most unspoiled, spectacular, and rugged countryside from Georgia to Maine. The peace and tranquility he hopes to find, though, is anything but, when the only person he can find willing to join him on the trek is his long-lost former friend Katz, a down-on-his-luck serial philanderer.